Strategi Pembelajaran Dalam Meningkatkan Kecerdasan Emosional Siswa di SMPIT Al-Fatih Cigombong - Thosin Balqis Zukhrufi Naida (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
Learning strategies in improving students' emotional intelligence, being an educator must have learning strategies that can improve their emotional intelligence, because strategy is a pattern that is planned and determined intentionally to carry out learning activities or actions by educators to students, while emotional intelligence is the ability which is specifically for reading the deepest feelings people are dealing with with the aim of dealing with relationships effectively and strategically. This study aims to determine what learning strategies are used by Smpit Al-Fatih to improve emotional intelligence. This research uses descriptive qualitative method, with data collection techniques of observation, interviews and documentation. The research subjects were school principals, BK (Counseling Counseling) teachers, learning teachers, and students. The results of the field show that the learning strategies used at Al Fatih Junior High School to improve their emotional intelligence use several programs. Learning strategies are using comparative learning with strategies that involve students in learning such as creating study groups that will make students more active, helping each other and helping each other. discussing, using technology and visualization using this strategy will provide encouragement to students in learning because it is easier to understand, understand the character of students, recognize students' emotions with all of this will better know the student's condition and can also apply learning in class, providing guidance to these students will make students' personalities even better, and learning aqidah morals with this learning will increase students' faith. Keywords: Emotional Intelligence, Strategy, Teacher.